2018
DOI: 10.1007/s00244-018-0561-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Lead Exposure in Four Avian Scavenger Species in Switzerland

Abstract: Despite irrefutable evidence of its negative impact on animal behaviour and physiology, lethal and sublethal lead poisoning of wildlife is still persistent and widespread. For scavenging birds, ingestion of ammunition, or fragments thereof, is the major exposure route. In this study, we examined the occurrence of lead in four avian scavengers of Switzerland and how it differs between species, regions, and age of the bird. We measured lead concentration in liver and bone of the two main alpine avian scavengers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
0
21
1
3
Order By: Relevance
“…The proportion of birds we detected with severe hepatic lead concentrations (6.6% were >20 mg/kg) is higher than those found in congeners (0-5.5%; Rodriguez-Ramos Fernandez et al, 2011;Jenni et al 2015;Madry et al 2015;Ganz et al 2018). In fact, we could find only one report of an individual liver lead concentration higher than the 181.6 mg/kg maximum detected in our study (243 mg/kg; Wayland et al 1999).…”
Section: Extent and Demographic Patterns Of Lead Exposurecontrasting
confidence: 82%
See 1 more Smart Citation
“…The proportion of birds we detected with severe hepatic lead concentrations (6.6% were >20 mg/kg) is higher than those found in congeners (0-5.5%; Rodriguez-Ramos Fernandez et al, 2011;Jenni et al 2015;Madry et al 2015;Ganz et al 2018). In fact, we could find only one report of an individual liver lead concentration higher than the 181.6 mg/kg maximum detected in our study (243 mg/kg; Wayland et al 1999).…”
Section: Extent and Demographic Patterns Of Lead Exposurecontrasting
confidence: 82%
“…Instead, because pre-adult birds have not lived long enough to exhibit signs of chronic exposure, it may be that the patterns in our data are driven by the predominance of pre-adult birds in our study. Pre-adults represented 76% of our sample, a notably higher proportion than in other studies assessing bone lead concentrations of raptors (e.g., 40% [Wayland et al 1999], 44% [Madry et al 2015] 44% [Ganz et al 2018], and 49% [Gangoso et al 2008]) or than would be expected from random sampling of a population of long-lived eagles (Katzner et al 2006). Bone lead concentrations reflect lifetime exposure due to the accumulation over time of lead in bone tissue (Fisher et al 2006).…”
Section: Extent and Demographic Patterns Of Lead Exposurementioning
confidence: 93%
“…Fourteen of 46 birds had bone Pb > 20 mg/kg. These lead burdens were higher than those found elsewhere in Europe or North America and compatible with acute lead poisoningGanz et al (2018)North America10% of 178 golden eagles captured during fall migration were clinically lead poisoned (PbB > 0.6 mg/l [60 µg/dl]) and 4% were lethally exposed (PbB > 1.2 mg/l [120 µg/dl]). PbB was higher in golden eagles captured on carrion than those captured using live baitLangner et al (2015)Northern SwedenPbB in wild birds was significantly correlated with the progress of the moose hunting season.…”
Section: Pathways Of Exposurementioning
confidence: 56%
“…104 µg/dl; bone lead* mean 22 ppm, max 148.20 ppm) compared with captive bred individuals (mean PbB 5.63 µg/dl, and mean bone lead* 2.76 ppm, n = 10). Two wild birds had lead in the gastrointestinal tract and 13 had lead fragments elsewhere in their bodies* sampled from live birdsWiemeyer et al (2017)ChileTwo birds reported with high PbB (one bird—89 µg/dl) and liver and kidney levels (one bird—136 and 247 ppm respectively) after ingesting lead bulletsBearded vulture Gypaetus barbatus Swiss AlpsTwo of five birds found dead had bone lead concentrations consistent with lead poisoning (59 and 100 mg/kg)Ganz et al (2018)White-backed vultures a Gyps africanus South Africa and NamibiaPbB compared in wild and captive birds. 12% of wild birds appeared to be exposed to an additional source of lead than purely environmental—presumed to be ammunitionNaidoo et al (2017)BotswanaPbB was analysed from 566 wild captured birds.…”
Section: Pathways Of Exposurementioning
confidence: 98%
“…In the case of lead, the study of species with similar, but not identical, feeding behaviors can provide insights into how an animal's ecology determines its lead exposure (Moreno‐Opo et al 2016). For example, a study in Switzerland illustrated how ecological factors such as habitat preference and feeding behavior can drive differing levels of lead exposure in multiple scavenging bird species (Ganz et al 2018).…”
Section: Introductionmentioning
confidence: 99%